2020
DOI: 10.1038/s41564-019-0632-1
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus cell growth and division are regulated by an amidase that trims peptides from uncrosslinked peptidoglycan

Abstract: Bacteria are protected by a polymer of peptidoglycan that serves as an exoskeleton 1. In Staphylococcus aureus, the peptidoglycan assembly enzymes relocate during the cell cycle from the periphery, where they are active during growth, to the division site where they build the partition between daughter cells 2-4. But how peptidoglycan synthesis is regulated throughout the cell cycle is poorly understood 5,6. Here we used a transposon screen to identify a membrane protein complex that spatially regulates S. aur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 59 publications
(130 reference statements)
1
80
0
Order By: Relevance
“…Previous work has shown that cell division defects result when S. aureus cells grow larger than normal (6, 42-45). Consistent with these findings, we observed a remarkable correlation between cell size and frequency of cell division defects for the mutants studied here.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work has shown that cell division defects result when S. aureus cells grow larger than normal (6, 42-45). Consistent with these findings, we observed a remarkable correlation between cell size and frequency of cell division defects for the mutants studied here.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were imaged at 30°C as described previously (45). For each field of view, 3 images were taken: 1) phase-contrast, 2) brightfield, and 3) fluorescence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations